Improvement of sensitivity band technique for worst case tolerance analysis of linear circuits - Sunun M. (2014)
This paper presents a method to improve the sensitivity band technique for worst case tolerance analysis of a linear circuit with uncertain circuit elements' values. These uncertain parameters can be represented as interval real numbers. By using the interval analysis and the sensitivity bands of monotonicity parameters, the number of uncertain parameters can be reduced. In case of non-monotonic parameters, a linear programming technique is applied to find the circuit response enclosure. From numerical experiments, the results of the proposed algorithm show sharper response enclosure than those obtained by using only the sensitivity band technique. And it still uses less computational time than the Monte-Carlo method. © 2008 IEEE.